Problematika Rumah Tangga Muallaf di Kota Pekanbaru dan Penyelesaiannya Perspektif Sosiologi Keluarga - Hanifah, Syifa; Arisman, Arisman; Azni, Azni (Jurnal Ilmiah Wahana Pendidikan, 2025)
Muallaf is the term for non-Muslims who have just converted to Islam. It is also interpreted as someone who receives guidance. Religion aims to provide guidance and guidance in living human life on this earth. Everyone has the right to determine the religion they believe in and also has the right to change their own choices and there is no element of coercion from anyone in choosing the religion they believe in. The problems faced by every convert to Islam are different and the efforts to solve them are also different. Therefore, there is special treatment for converts to Islam, for example being able to receive zakat without having to pay attention to their economic situation is entitled to receive guidance about Islam until they are able and receive the same treatment in the social environment even though they have the status of a convert. Because basically deciding to embrace any religion is regulated in the laws of the Republic of Indonesia. The type of research in this research is field research, namely research that examines applicable legal provisions and what happens in reality in society. In this research the author used qualitative data analysis with descriptive methods. The results of this research show that Muslim households in Pekanbaru City face a number of challenges that can determine family harmony and welfare. One of the main challenges is rejection from the family and social environment after embracing Islam, experiencing a decline in the economy due to losing the facilities provided by the family and even losing one's job. The research also found that religious formation efforts, especially through the An-Nur Center for Muallaf Institutions in Pekanbaru City, have an important role in helping overcome this problem.